Morphological and Molecular Identification of Sarcocystis arctica in Captive Cheetahs (Acinonyx jubatus) in China Helps Clarify Phylogenetic Relationships with Sarcocystis caninum and Sarcocystis felis - Zhe Liao; Niuping Zhu; Yurong Yang; Shuangsheng Deng; Thomas Jäkel; Junjie Hu (Animals)
To date, only one case is known where protozoan parasites of the genus Sarcocystis were found to infect cheetahs (Acinonyx jubatus); the cysts in the musculature were morphologically identified as S. felis. Here, we characterized sarcocysts by morphological and molecular methods that were observed in cheetahs who died in zoos in China. Only one type of sarcocyst was present in two of six cheetahs. By light microscopy, the sarcocyst wall was striated, 1.4–2.1 μm thick. Ultrastructurally, the wall had irregular-shaped, small villar protrusions, resembling wall type 9c, similar to those of S. arctica, S. caninum, and S. felis. The samples shared their highest molecular identity values with those of S. arctica and S. caninum: 99.9–100% and 99.8–100% (18S rRNA), 99.5% and 99.3–99.5% (28S rRNA), 95.9–97.5% and 96.3–97.3% (ITS-1), and 99.6% and 99.2–99.7% (cox1), respectively. Compared with ITS-1 of S. felis, identities ranged between 87.5% and 88.9%. Phylogenetic reconstruction revealed that the newly sequenced Sarcocystis clustered with S. arctica and S. caninum, whereas S. felis (ITS-1) and S. canis (ITS-1, 18S rRNA, cox1) were sister species. Thus, we addressed the Sarcocystis species from the cheetahs as S. arctica, which is the first record of a Sarcocystis species believed to be specific for canids as intermediate hosts to infect a feline host.